The Determinants of Corporate Debt Maturity Structure. the Case of Chile [Los Determinantes de la Estructura de la Madurez de la Deuda Corporativa. el Caso de Chile] - Castaneda-Gonzalez, F (Fondo de Cultura Economica, 2017)
Background: The aim of this article is to provide an empirical examination of the determinants of debt maturity over a one year term for Chile. The debt to be considered is that issued as fixed income by Chilean companies listed on the Santiago Stock Exchange. This research is conducted within a theoretical framework of agency costs, tax hypothesis, and debt signaling hypothesis. Methods: To carry out the analysis, we will employ a panel of data based on annual financial information for the period between 2002 and 2012 obtained from Bloomberg. With this, we perform a pooled regression, a model with fixed-effects, and another with random-effects. Results: After analyzing a sample of 434 observations for 50 companies with 52.8% of their debt having a maturity greater than one year, an asset maturity of 29.26 years, and an effective tax rate of 18.2%, we fnd the following results. The ratio between the market value and the book value is statistically significant and has the expected negative sign. We find that both size and regulation are statistically significant and have a positive sign. The results obtained for the tax variable indicate that it is not statistically significant, which is consistent with international evidence. Furthermore, the estimated coefficient for the maturity of assets is not statistically significant, which contradicts some of the ideas proposed by Myers (1977). The quality variable is statistically significant at the 5 percent level of significance in all of the regressions; however, it does not have the expected negative sign. Finally, most of the results are consistent with the international evidence; hence, the determinants of debt maturity in Chile are similar to those found in other countries, such as the US, the UK and Spain. Conclusions: Large frms (and/or those whose size is regulated) with low growth opportunities have a greater proportion of their debt with a maturity of more than one year. The evidence also suggests that frms exposed to high information asymmetries issue proportionally more short-term than long-term debt. Meanwhile, we found no conclusive evidence that frms seek to match the maturity of their assets with that of their debt, or that they seek to issue debt with a maturity of more than one year in order to take advantage of tax benefts.